2018
DOI: 10.1111/bcpt.13015
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide‐Releasing Molecule Enhances Coagulation and Decreases Fibrinolysis in Normal Canine Plasma

Abstract: The dog is an important companion animal and also purpose-bred for research studies. Coagulopathies in dogs are common, although the availability of blood products for therapy is inconsistent throughout the profession. A pro-coagulant therapeutic that is readily available and easily stored would be useful for the treatment of coagulopathies. Tricarbonyldichlororuthenium (II) dimer [Carbon monoxide-releasing molecule-2 (CORM-2)] acts as a prothrombotic agent in plasma by increasing the velocity of clot formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…2,3,25,27 These reports did not describe the effects of these molecules on venom-induced hyperfibrinolysis. We have previously shown that CORM-2 enhances coagulation and decreases fibrinolysis in individual canine plasma in vitro, 24 and have not previously tested FeCl 3 and therefore tested whether CORM-2 could mitigate C viridis venom-induced coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,25,27 These reports did not describe the effects of these molecules on venom-induced hyperfibrinolysis. We have previously shown that CORM-2 enhances coagulation and decreases fibrinolysis in individual canine plasma in vitro, 24 and have not previously tested FeCl 3 and therefore tested whether CORM-2 could mitigate C viridis venom-induced coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,22,23 Previous findings of the clot strengthening effects of CO led us to hypothesize that CO may be able to strengthen clot formation in plasma from normal dogs exposed to Prairie rattlesnake (Crotalus viridis) venom and in plasma from naturally envenomed dogs. 24 To date, CORM-2 has been shown to mitigate coagulopathy induced by several crotalid venoms in human plasma. 3,[25][26][27] Coagulopathy is a common sequel to rattlesnake bites in human beings and canine victims.…”
Section: Introductionmentioning
confidence: 99%